A Review On Product Development Of Islamic Social Finance In Tijari Sector - Syahidawati Hj. Shahwan; Zurina Shafii; Safeza Mohd Sapian; Supiah Salleh; Norhaziah Nawai; Norhazlina Ibrahim; Asmaddy Haris; Azrul Azlan Iskandar Mirza; Norafni @ Farlina Rahim (Islamic Business School, Universiti Utara Malaysia, 2024)
Non-Indexed Publication